MAL DE OJO AND ITS RELATIONSHIP WITH MARASM AND KWASHIORKOR: THE TURBO MOTHER’S CASE - Uribe Gil, Gildardo; Alcaraz López, Gloria Margarita (Investigación y Educación en Enfermería, 2008)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Objective: To describe perceptions and sociocultural practices by the mothers facing severe malnutrition in children: Marasm and Kwashiorkor. Methodology: Descriptive ethnography. Twenty semi-structured interviews and two tribal ones were carried. Homes and hospitalized children were observed. Analysis was manually performed. Results: Mother perceives severe malnutrition like “mal de ojo” consequence af.icting children under seven. Mal de ojo is classi.ed as “drying-eye” or as “street-eye”. Mothers think that “drying-eye” emaciates children meaning something like what we call marasm, whereas we cannot tell weather “street-eye” means kwashiorkor; but in any case kwashiorkor is deemed to be caused by mal de ojo. “Traditional” medics like rezanderos perform important tasks in the treatment of cultural linked illnesses. Conclusions: Malnourishment is considered a “state” and .nally it is reduced to statistical data hindering the integral treatment of children. The study reveals a world unknown by the biomedical system and a world of cultural practices facing malnourishment that adequately assessed could improve integral treatment and prevent infant mortality by severe malnourishment or by mal de ojo